2013
DOI: 10.1080/19392699.2012.759944
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Effective Parameters on the Gas Holdup in Column Flotation of a Coal Tailing Sample

Abstract: This study presents the results of gas holdup investigation in a laboratory column flotation cell that was fed by coal tailings. The effect of process variables such as gas flow rate, feed flow rate, wash water flow rates, collector dosage, and frother dosage was investigated on the gas holdup. In this study, the pressure transducers were used to estimate the gas holdup in the column. Gas holdup was found to be strongly dependent on the superficial gas velocity. It was increased with increasing feed rate and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The obtained trends of gas hold-up changes with solid content are similar to the literature data presented by Bahri et al [13], Bhunia et al [12], Banisi et al [16], Tavera and Escudero [27]. Bahri et al [13] and Bhunia et al [12] performed the experiments to study the influence of slurry and air flowrate in the collection zone and found that gas hold-up increases with air and slurry flowrates for coal. In addition to that, the gas hold-up increases with the addition of frother concentration.…”
Section: Hydrophilic Silica Slurry Experimentssupporting
confidence: 85%
See 1 more Smart Citation
“…The obtained trends of gas hold-up changes with solid content are similar to the literature data presented by Bahri et al [13], Bhunia et al [12], Banisi et al [16], Tavera and Escudero [27]. Bahri et al [13] and Bhunia et al [12] performed the experiments to study the influence of slurry and air flowrate in the collection zone and found that gas hold-up increases with air and slurry flowrates for coal. In addition to that, the gas hold-up increases with the addition of frother concentration.…”
Section: Hydrophilic Silica Slurry Experimentssupporting
confidence: 85%
“…Although influence of solids concentration on the gas hold-up change was predicted as similar to the experimental data, but mostly speculated the mechanism beyond the gas hold change without showing detailed evidence. Bahri et al [13] discussed that gas dispersion was dependent on gas superficial velocity, frother dosage and feed flowrate in coal tailings process. The gas hold-up increased by all above-mentioned parameters.…”
Section: Introductionmentioning
confidence: 99%